Partial Purification of Thermophilic Pectinase from Local Isolate Anoxybacillus flavithermus TP-01 - Galih Ayhusta Laras; Ismi Aulia Syafira; Afaf Baktir; Putri, Kartika Dwi Asni (Universitas Airlangga, 2022)
Pectinase is an enzyme that can hydrolyze substances of pectin. It has several applications in daily life, for example in juice factories, wine factories, pulp and paper factories, coffee and tea factories that use fermentation. Pectinase consists of pectate lyase, pectin lyase, and polygalacturonase. The aim of this research is to partially purify pectinase protein by ammonium sulfate precipitation and dialysis. A preliminary test of pectinase activity used halo zone analysis. The partial purification was needed to optimize ammonium sulfate and get the optimal condition in 40–90% of the ammonium sulfate composition. Pectinase activity was measured using DNS method, and the concentration of protein was measured using Bradford method. The result of this partial purification of Anoxybacillus flavithermus TP-01 was 70%. Decreasing od pectinase activity was resulted in this research due to the loss of cofactor. Based on the result, it can be concluded that the pectinase from Anoxybacillus flavithermus TP-01 was polygalacturonase.